Unravelling the Mysteries of the Mesentery - Gopalan, Sunita; Raghu, Vineetha (Journal of Gastrointestinal and Abdominal Radiology, 2020)
The mesentery and its folds tether the small bowel loops to the posterior abdominal wall. It transmits nerves, vessels, and lymph ensconced in a fatty sponge layer wrapped in a thin glistening peritoneum, from and to the small bowel. Not only does this flexible dynamic fatty apron house various localized primary benign and malignant lesions, it is often involved in and gives an indication of generalized or systemic diseases in the body. An understanding of the anatomy, components, and function of the mesentery helps to classify mesenteric abnormalities. This further allows for characterizing radiological patterns and appearances specific to certain disease entities. Recent reviews of mesenteric anatomy have kindled new interest in its function and clinical applications, heralding the possibility of revision of its role in diseases of the abdomen.
Keywords: mesentery; diseases; masses; nonneoplastic